Calcium-Binding Proteins as Determinants of Central Nervous System Neuronal Vulnerability to Disease - Fairless, Richard; Williams-Fairless, Sarah K.; Diem, Ricarda (International journal of molecular sciences, 2019)
Neuronal subpopulations display differential vulnerabilities to disease, but the factors that determine their susceptibility are poorly understood. Toxic increases in intracellular calcium are a key factor in several neurodegenerative processes, with calcium-binding proteins providing an important first line of defense through their ability to buffer incoming calcium, allowing the neuron to quickly achieve homeostasis. Since neurons expressing different calcium-binding proteins have been reported to be differentially susceptible to degeneration, it can be hypothesized that rather than just serving as markers of different neuronal subpopulations, they might actually be a key determinant of survival. In this review, we will summarize some of the evidence that expression of the EF-hand calcium-binding proteins, calbindin, calretinin and parvalbumin, may influence the susceptibility of distinct neuronal subpopulations to disease processes.